Pengembangan Media Pembelajaran Google Sites Berbasis STEM Materi Pencemaran Lingkungan Kelas X SMA Negeri Bali Mandara - Fransiska Yunita Sembung; Ida Bagus Putu Arnyana; Sanusi Mulyadiharja (Jurnal Pendidikan Biologi Undiksha, 2022)
This study aims to determine (1) the design of the STEM-based Google Sites learning media on the subject of environmental pollution in class X SMA Negeri Bali Mandara, (2) the validity of the development of STEM-based Google Sites learning media on the subject of environmental pollution in class X SMA Negeri Bali Mandara. and (3) the practicality of developing STEM based Google Sites learning media on the subject of environmental pollution in class X SMA Negeri Bali Mandara. This type of research is development research (R & D) which refers to the ADDIE development model which includes the analysis, design and development stages. The validity test was carried out involving language, media and material experts. Practicality test which consists of practicality test for teachers and students. The product test subjects in this study were students of class X MIPA 2. Data analysis was carried out descriptively to determine the validity and practicality. The results showed, (1) the results of each stage of development produced a product in the form of Google Sites learning media based on the STEM approach (2) the results of the language validity test were 4.84 followed by the media validity test of 4.52 and the material validity test of 4.66 which the total average value of 4.67 is declared very valid (3) the practicality test of teachers is 91.76% very practical and the practicality test of students is 86.44 % very practical then the results of the average value of total practicality are 88.10% stated to be very practical. Based on the results of the study, in the form of Google Sites learning media based on the STEM approach that was developed, it is very valid and very practical to use as a learning medium for environmental pollution material for class X SMA Negeri Bali Mandara.